PENGEMBANGAN MEDIA VIDEO CERDAM SEBAGAI MEDIA EDUKASI PENCEGAHAN DIABETES MELITUS DI POSBINDU TERATAI CILEBUT BOGOR - Nafilah Nur Qonitah; Neng Ayu Rosita (Jurnal Kesehatan Siliwangi, 2024)
Background: Diabetes Mellitus data for West Java is 863,903 in 2023. So the number of Diabetes Mellitus sufferers seen from year to year in the city of Bogor is 111,577. The data for 2023 is the highest. The number of diabetes sufferers at Posbindu Teratai is 25 people. Objective: Develop clever video media to prevent diabetes. Method: Development of RND with a 4D model includes a total sampling technique and data collection is carried out using in-depth interviews. Results: At the Define stage, media is needed that is interesting, informative, images that can move and also bright colors. In the Design stage, video media was used using the Canva application, capcut with a duration of 4 minutes 2 seconds. In the Development stage, material experts tested with 90% results, media experts with 96% results and development trials with 98% results, meaning the media was "very feasible used". At the Disseminate stage it is distributed using the YouTube application. Conclusion: Define requires media that is interesting, informative, images that can move and also bright colors. In the Design stage, video media was used using the Canva application, Capcut with a duration of 4 minutes 2 seconds. In the Development stage, material experts, media experts and development trials were tested. At the Disseminate stage it is distributed using the YouTube application.